Liberating Oppressors: The Toughest Task of Full Reconciliation - Karanovich, R Zachary (Lumen et Vita, 2018)
The process of reconciliation is necessarily centered on the victim. But Jürgen Moltmann rightly states that, “Oppression always has two sides. ” Insofar as one can envision the tasks of liberation and reconciliation to be at least parallel, a premise that this paper acknowledges, then liberation too must be forward thinking. To redeem the past, Moltmann argued that we must not only seek the liberation of the oppressed, but also the liberation of the oppressor. The preferential option for the victim is indeed necessary, but so too is the transformation of the oppressor. While this application of liberation on the side of the oppressor is not always warmly received by liberation thinkers, Jon Sobrino also stated the need for a continued openness to the oppressor as essential to reconciliation and the liberation spirituality. This paper will draw on theological, literary, and historical sources as well as current events to explore the status of this sometimes controversial question of the liberation of the oppressor and its place within the goal of reconciliation.